The effect of learning with a realistic mathematical approach on students mathematical communication skills in the material algebra - Faizah, Hanim; Sugandi, Eko (UNIVERSITAS NEGERI MALANG, 2023)
This study aims to determine the effect of a realistic mathematical approach on students' mathematical communication skills, especially in algebraic material. This research was conducted at SMP Negeri 21 Surabaya, with a sample of 72 students in VII class and divided into two classes, namely the experimental class, which applied a realistic mathematical approach, and the control class, which applied the scientific approach. After learning, students are given a test of students mathematical communication tests and analyzed using a t-test to determine if there are differences in the results of students' mathematical communication tests between the two classes. The study's results revealed differences in students’ mathematical communication tests between the experimental and control classes. Furthermore, based on the average results of the mathematics communication test, the students showed that the experimental class was higher than the control class. So the realistic mathematics approach has a better effect on students' mathematical communication than the scientific approach.